A functionally significant SNP in TP53 and breast cancer risk in African-American women - Maureen E. Murphy; Song Liu; Song Yao; Dezheng Huo; Qin Liu; Sonia C. Dolfi; Kim M. Hirshfield; Chi-Chen Hong; Qiang Hu; Andrew F. Olshan; Temidayo O. Ogundiran; Clement Adebamowo; et al. (npj Breast Cancer, 2017)
Genetics: Variant may increase cancer risk in pre-menopausal black women A gene variant found in people of African descent may increase the risk of breast cancer—but only among pre-menopausal women. In a study of more than 14,000 women of African ancestry, a team led by Maureen Murphy from the Wistar Institute in Philadelphia, Pennsylvania, USA, and Christine Ambrosone from Roswell Park Cancer Institute in Buffalo, NY, USA, tested for an association between breast cancer and a rare genetic polymorphism in the TP53 gene that’s found almost exclusively in African-descent populations. This variant alters the p53 tumor suppressor protein and has been shown to increase cancer risk in a mouse model. Murphy and colleagues showed that the variant increased risk by about 72% in women who had not yet experienced menopause—which could help explain the earlier onset of the disease among women of African ancestry.